Clinical characteristics and prognosis of patients with antiphospholipid antibodies based on cluster analysis: an 8-year cohort study - Qi, Wanting; Zhao, Jiuliang; Huang, Can; Jiang, Nan; Li, Jing; Wu, Chanyuan; Zhang, Shangzhu; Hu, Chaojun; Xu, Dong; Wang, Qian; Li, Mengtao; Tian, Xinping; et al. (Arthritis research & therapy, 2022)
Antiphospholipid syndrome (APS) is an autoimmune disease characterized by persistent antiphospholipid antibodies (aPLs) positivity with a wide manifestation spectrum. A risk stratification is needed for management guidance and prognosis assessment. We aimed to identify phenotypes among aPL-positive patients and assess the prognosis of each phenotype. This was a single-center, prospective cohort study of aPL-positive patients presented to Peking Union Medical College Hospital from 2012 to 2020. Demographic characteristics, aPL-related manifestations, cardiovascular risk factors, and antibodies profiles were recorded. The primary endpoint was defined as a combination of newly onset thrombosis, major bleeding events, non-criteria manifestations, and all-cause death. Hierarchical cluster analysis and Kaplan-Meier survival analysis were performed. Four clusters among 383 patients (70.2% female; mean age 37.7 years) were identified. Cluster 1 (n = 138): patients with systemic lupus erythematosus (SLE) and non-criteria manifestations; cluster 2 (n = 112): patients with multiple cardiovascular risk factors; cluster 3 (n = 83): female patients with obstetric morbidity; cluster 4 (n = 50): patients with isolated lupus anticoagulant (LA) positivity. Non-criteria manifestations were found aggregated with SLE from cluster analysis of variables. Cluster 3 showed the best outcome, while cluster 2 suffered highest frenquency of newly onset arterial thrombosis. We identified 4 clinical phenotypes of aPL-positive patients. Non-criteria manifestations may indicate underlying SLE, for which immunosuppressive therapy besides anticoagulation may be necessary. Patients with isolated LA positivity suffered similar risks with secondary APS and patients with multiple cardiovascular risk factors. Attention should be paid to male patients, and the screening of cardiovascular risk factors should never be ignored.